RANCANG BANGUN APLIKASI PENGAJUAN SIMPAN PINJAM PADA KOPERASI SIMPAN PINJAM DANA ARTA MANDIRI BERBASIS WEBSITE - Muhammad Bismar Affandi (LKP KARYA PRIMA KURSUS, 2025)
One of the cooperatives in Medan City is the Dana Arta Mandiri Savings and Loans Cooperative, which is an economic financial institution. The services available at this cooperative are savings and loans and cash bonds. However, this research only discusses one thing provided by the company, namely savings and loan application services. The various products provided by this cooperative are savings and loan services. Currently, the process of managing savings and loan data is still manual, that is, members have to visit the cooperative to ask for savings and loan information and it is difficult to register members which cannot be accessed online. This causes the data management process in the Dana Arta Mandiri Savings and Loans Cooperative to be less effective and efficient. However, the management process does not yet have an adequate information system. Where the information system for savings and loan cooperatives has not made it easy to collect data, process data and present information on savings and loan cooperatives. Current transaction information services are still carried out manually. Problems that occur in the savings and loan system of the Dana Arta Mandiri Savings and Loans Cooperative are processing customer data and searching for customer data which takes quite a long time, determining payment fines, implementing payments, reporting customer data and payments and processing customer savings and loan data.